The Impact of International Standards IAES on Activating Continuing Accounting Education in The Iraqi Environment - Hussein Ali Mohammed; Khalid Hamad Jasim Al-Shaikh (Eximia, 2024)
The accounting profession faces many challenges in the age of knowledge, as some of how the accounting function accomplishes its tasks have changed, which raised the question about the importance and value of traditional accounting jobs and skills, which require adopting ideas, work methods, and applications that differ from those previously, in addition to possessing qualifications and skills that were previously unknown. It is necessary to have them in the past. Therefore, there must be references and standards that contribute to the development of the accounting profession, represented by the accounting education standards (IAES), which have a positive impact on the quality of accounting service and activate the continuing education process so that the required task can be presented appropriately, as the continuing education system must have clear goals and outcomes that meet the needs of the labour market for specialists in the field of practising the accounting profession following the requirements of the current era. Continuing professional development for professional accountants enhances competence, skill and all outcomes of accounting work. Compliance with the International Standards for Accounting Education (IAES) and the application of continuing professional educational requirements by the accountant can also lead to Enhancing the accuracy and reliability of accounts, which is among the most important areas of need in developing the accounting profession, improving training programs for accountants, and modernising the training process. It is also desirable to provide continuous professional development. It is possible to develop a strategic plan for employment and organise the monitoring of its implementation. The research was based on a form distributed to the research community represented by the Federation Accountants and auditors in Iraq at the time. The most important conclusion of the research is that the application of international accounting education standards contributes to raising the efficiency and professional skills of accountants. The research concluded that the Union of Accountants and Auditors in Iraq supports the application of international accounting education standards by all accountant members of the Union. The research dealt with a group of sections, the first section included the research methodology and previous studies, the second section included the theoretical aspect of the research, the third section included the applied aspect, and finally, the fourth section included recommendations and conclusions.